Green Service Consumption: Unlocking Customer Expectations on Technological Transformations Enhancing Purchase Experience in Retail Store - Arjun J Nair; Sridhar Manohar (International Journal of Information Management Data Insights)
The research delves into the intricacies of green service consumption within the retail sector, concentrating specifically on delineating customer expectations and elucidating the transformative technological interface. The study elucidates the intricate dynamics of customer expectations and technological transformations to enhance the purchase experience in retail stores, focusing on the evolving paradigm in the retail landscape from a product-centric to a service-oriented economy and unveiling the pivotal role of societal influences, technology and customer expectations. The central theme revolves around understanding green service consumption within the retail sector, emphasizing the interplay between societal values, technological innovations and the dynamism of customer expectations. The research design employed is qualitative, leveraging a multidisciplinary approach and gleaning insights from sociotechnical perspectives, environmental sustainability, AI and consumer behavior. The sampling design involved experts in the field who participated in interviews and were purposefully selected based on their expertise in green service consumption and retail practices. The analysis utilized the fuzzy DEMANTEL method, involving a rudimentary exploration of dimensions. The research leverages extensive and in-depth deliberations involving theoretical explorations, connections among influencing factors and methodological insights from fuzzy logic and DEMATEL to dissect the complexities of green service consumption. The study elucidates the pivotal transition in the retail landscape, unveiling the changing nature of customer expectations, the surging significance of green service consumption and the influence of societal values and technological advancements. The discourse signifies the paramount role of societal values, particularly the increasing awareness of sustainability, ethical sourcing and eco-friendly strategies, in shaping retail strategies. The research presents a multifaceted view of green service consumption, thereby contributing to an enriched theoretical landscape of green service-focused retail experiences.